continuing to revise Stlc and StlcProp

This commit is contained in:
Philip Wadler 2017-07-11 13:55:00 +01:00
parent eceafb86eb
commit c059b831af
2 changed files with 145 additions and 164 deletions

View file

@ -34,7 +34,7 @@ infix 15 λ[__]_
infix 15 if_then_else_
data Term : Set where
var : Id → Term
` : Id → Term
λ[__]_ : Id → Type → Term → Term
_·_ : Term → Term → Term
true : Term
@ -49,8 +49,8 @@ f = id 0
x = id 1
not two : Term
not = λ[ x 𝔹 ] (if var x then false else true)
two = λ[ f 𝔹𝔹 ] λ[ x 𝔹 ] var f · (var f · var x)
not = λ[ x 𝔹 ] (if ` x then false else true)
two = λ[ f 𝔹𝔹 ] λ[ x 𝔹 ] ` f · (` f · ` x)
\end{code}
## Values
@ -66,9 +66,9 @@ data Value : Term → Set where
\begin{code}
_[_=_] : Term → Id → Term → Term
(var x) [ x = V ] with x ≟ x
(` x) [ x = V ] with x ≟ x
... | yes _ = V
... | no _ = var x
... | no _ = ` x
(λ[ x A ] N) [ x = V ] with x ≟ x
... | yes _ = λ[ x A ] N
... | no _ = λ[ x A ] (N [ x = V ])
@ -84,22 +84,22 @@ _[_=_] : Term → Id → Term → Term
infix 10 _⟹_
data _⟹_ : Term → Term → Set where
β : ∀ {x A N V} → Value V →
βλ· : ∀ {x A N V} → Value V →
(λ[ x A ] N) · V ⟹ N [ x = V ]
γ⇒₁ : ∀ {L L' M} →
L ⟹ L'
L · M ⟹ L' · M
γ⇒₂ : ∀ {V M M'} →
ξ·₁ : ∀ {L L M} →
L ⟹ L
L · M ⟹ L · M
ξ·₂ : ∀ {V M M} →
Value V →
M ⟹ M'
V · M ⟹ V · M'
β𝔹₁ : ∀ {M N} →
M ⟹ M
V · M ⟹ V · M
βif-true : ∀ {M N} →
if true then M else N ⟹ M
β𝔹₂ : ∀ {M N} →
βif-false : ∀ {M N} →
if false then M else N ⟹ N
γ𝔹 : ∀ {L L' M N} →
L ⟹ L'
if L then M else N ⟹ if L' then M else N
ξif : ∀ {L L M N} →
L ⟹ L
if L then M else N ⟹ if L then M else N
\end{code}
## Reflexive and transitive closure
@ -117,26 +117,26 @@ data _⟹*_ : Term → Term → Set where
reduction₁ : not · true ⟹* false
reduction₁ =
not · true
⟹⟨ β value-true ⟩
⟹⟨ βλ· value-true ⟩
if true then false else true
⟹⟨ β𝔹₁
⟹⟨ βif-true
false
reduction₂ : two · not · true ⟹* true
reduction₂ =
two · not · true
⟹⟨ γ⇒₁ (β⇒ value-λ) ⟩
(λ[ x 𝔹 ] not · (not · var x)) · true
⟹⟨ β value-true ⟩
⟹⟨ ξ·₁ (βλ· value-λ) ⟩
(λ[ x 𝔹 ] not · (not · ` x)) · true
⟹⟨ βλ· value-true ⟩
not · (not · true)
⟹⟨ γ⇒₂ value-λ (β⇒ value-true) ⟩
⟹⟨ ξ·₂ value-λ (βλ· value-true) ⟩
not · (if true then false else true)
⟹⟨ γ⇒₂ value-λ β𝔹₁
⟹⟨ ξ·₂ value-λ βif-true
not · false
⟹⟨ β value-false ⟩
⟹⟨ βλ· value-false ⟩
if false then false else true
⟹⟨ β𝔹₂
⟹⟨ βif-false
true
\end{code}
@ -156,7 +156,7 @@ infix 10 _⊢__
data _⊢__ : Context → Term → Type → Set where
Ax : ∀ {Γ x A} →
Γ x ≡ just A →
Γ ⊢ var x A
Γ ⊢ ` x A
⇒-I : ∀ {Γ x N A B} →
Γ , x A ⊢ N B →
Γ ⊢ λ[ x A ] N A ⇒ B
@ -201,19 +201,19 @@ the outermost term in `not` in a `λ`, which is typed using `⇒-I`. The
`⇒-I` rule in turn takes one argument, which Agda leaves as a hole.
typing₁ = ⇒-I { }0
?0 : ∅ , x 𝔹 ⊢ if var x then false else true 𝔹
?0 : ∅ , x 𝔹 ⊢ if ` x then false else true 𝔹
Again we fill in the hole by typing C-c C-r. Agda observes that the
outermost term is now `if_then_else_`, which is typed using `𝔹-E`. The
`𝔹-E` rule in turn takes three arguments, which Agda leaves as holes.
typing₁ = ⇒-I (𝔹-E { }0 { }1 { }2)
?0 : ∅ , x 𝔹var x
?0 : ∅ , x 𝔹` x
?1 : ∅ , x 𝔹 ⊢ false 𝔹
?2 : ∅ , x 𝔹 ⊢ true 𝔹
Again we fill in the three holes by typing C-c C-r in each. Agda observes
that `var x`, `false`, and `true` are typed using `Ax`, `𝔹-I₂`, and
that `\` x`, `false`, and `true` are typed using `Ax`, `𝔹-I₂`, and
`𝔹-I₁` respectively. The `Ax` rule in turn takes an argument, to show
that `(∅ , x 𝔹) x = just 𝔹`, which can in turn be specified with a
hole. After filling in all holes, the term is as above.

View file

@ -81,32 +81,32 @@ _Proof_: By induction on the derivation of `∅ ⊢ M A`.
hypotheses. By the first induction hypothesis, either `L`
can take a step or is a value.
- If `L` can take a step, then so can `L · M` by `γ⇒₁`.
- If `L` can take a step, then so can `L · M` by `ξ·₁`.
- If `L` is a value then consider `M`. By the second induction
hypothesis, either `M` can take a step or is a value.
- If `M` can take a step, then so can `L · M` by `γ⇒₂`.
- If `M` can take a step, then so can `L · M` by `ξ·₂`.
- If `M` is a value, then since `L` is a value with a
function type we know from the canonical forms lemma
that it must be a lambda abstraction,
and hence `L · M` can take a step by `β`.
and hence `L · M` can take a step by `βλ·`.
- If the last rule of the derivation is `𝔹-E`, then the term has
the form `if L then M else N` where `L` has type `𝔹`.
By the induction hypothesis, either `L` can take a step or is
a value.
- If `L` can take a step, then so can `if L then M else N` by `γ𝔹`.
- If `L` can take a step, then so can `if L then M else N` by `ξif`.
- If `L` is a value, then since it has type boolean we know from
the canonical forms lemma that it must be either `true` or
`false`.
- If `L` is `true`, then `if L then M else N` steps by `β𝔹₁`
- If `L` is `true`, then `if L then M else N` steps by `βif-true`
- If `L` is `false`, then `if L then M else N` steps by `β𝔹₂`
- If `L` is `false`, then `if L then M else N` steps by `βif-false`
This completes the proof.
@ -114,26 +114,26 @@ This completes the proof.
progress (Ax ())
progress (⇒-I ⊢N) = done value-λ
progress (⇒-E ⊢L ⊢M) with progress ⊢L
... | steps L⟹L = steps (γ⇒₁ L⟹L)
... | steps L⟹L = steps (ξ·₁ L⟹L)
... | done valueL with progress ⊢M
... | steps M⟹M = steps (γ⇒₂ valueL M⟹M)
... | steps M⟹M = steps (ξ·₂ valueL M⟹M)
... | done valueM with canonicalFormsLemma ⊢L valueL
... | canonical-λ = steps (β valueM)
... | canonical-λ = steps (βλ· valueM)
progress 𝔹-I₁ = done value-true
progress 𝔹-I₂ = done value-false
progress (𝔹-E ⊢L ⊢M ⊢N) with progress ⊢L
... | steps L⟹L = steps (γ𝔹 L⟹L)
... | steps L⟹L = steps (ξif L⟹L)
... | done valueL with canonicalFormsLemma ⊢L valueL
... | canonical-true = steps β𝔹₁
... | canonical-false = steps β𝔹₂
... | canonical-true = steps βif-true
... | canonical-false = steps βif-false
\end{code}
This code reads neatly in part because we look at the
This code reads neatly in part because we consider the
`steps` option before the `done` option. We could, of course,
look at it the other way around, but then the `...` abbreviation
do it the other way around, but then the `...` abbreviation
no longer works, and we will need to write out all the arguments
in full. In general, the rule of thumb is to look at the easy case
(here `steps`) before the hard case (her `done`).
in full. In general, the rule of thumb is to consider the easy case
(here `steps`) before the hard case (here `done`).
If you have two hard cases, you will have to expand out `...`
or introduce subsidiary functions.
@ -158,20 +158,20 @@ technical lemmas), the story goes like this:
- The _preservation theorem_ is proved by induction on a typing
derivation, pretty much as we did in the [Types]({{ "Types" | relative_url }})
chapter. The one case that is significantly different is the one for the
` rule, whose definition uses the substitution operation. To see that
λ·` rule, whose definition uses the substitution operation. To see that
this step preserves typing, we need to know that the substitution itself
does. So we prove a ...
- _substitution lemma_, stating that substituting a (closed)
term `V` for a variable `x` in a term `N` preserves the type
of `N`. The proof goes by induction on the form of `N` and
requires looking at all the different cases in the definition
of substitition. The tricky cases are the ones for
variables and for function abstractions. In both cases, we
discover that we need to take a term `V` that has been shown
to be well-typed in some context `Γ` and consider the same
term in a different context `Γ′`. For this
we prove a...
- _substitution lemma_, stating that substituting a (closed) term
`V` for a variable `x` in a term `N` preserves the type of `N`.
The proof goes by induction on the form of `N` and requires
looking at all the different cases in the definition of
substitition. The lemma does not require that `V` be a value,
though in practice we only substitute values. The tricky cases
are the ones for variables and for function abstractions. In both
cases, we discover that we need to take a term `V` that has been
shown to be well-typed in some context `Γ` and consider the same
term in a different context `Γ′`. For this we prove a ...
- _context invariance_ lemma, showing that typing is preserved
under "inessential changes" to the context---a term `M`
@ -180,8 +180,8 @@ technical lemmas), the story goes like this:
And finally, for this, we need a careful definition of ...
- _free variables_ of a term---i.e., those variables
mentioned in a term and not in the scope of an enclosing
function abstraction binding a variable of the same name.
mentioned in a term and not bound in an enclosing
lambda abstraction.
To make Agda happy, we need to formalize the story in the opposite
order.
@ -190,19 +190,19 @@ order.
### Free Occurrences
A variable `x` appears _free_ in a term `M` if `M` contains an
occurrence of `x` that is not bound in an outer lambda abstraction.
occurrence of `x` that is not bound in an enclosing lambda abstraction.
For example:
- `x` appears free, but `f` does not, in `λ[ f (𝔹𝔹) ] var f · var x`
- both `f` and `x` appear free in `(λ[ f (𝔹𝔹) ] var f · var x) · var f`;
note that `f` appears both bound and free in this term
- no variables appear free in `λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] var f · var x`
- `x` appears free, but `f` does not, in `λ[ f (𝔹𝔹) ] ` f · ` x`
- both `f` and `x` appear free in `(λ[ f (𝔹𝔹) ] ` f · ` x) · ` f`;
indeed, `f` appears both bound and free in this term
- no variables appear free in `λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] ` f · ` x`
Formally:
\begin{code}
data _∈_ : Id → Term → Set where
free-var : ∀ {x} → x ∈ var x
free-` : ∀ {x} → x ∈ ` x
free-λ : ∀ {x y A N} → y ≢ x → x ∈ N → x ∈ (λ[ y A ] N)
free-·₁ : ∀ {x L M} → x ∈ L → x ∈ (L · M)
free-·₂ : ∀ {x L M} → x ∈ M → x ∈ (L · M)
@ -227,10 +227,10 @@ Here are proofs corresponding to the first two examples above.
f≢x : f ≢ x
f≢x ()
example-free₁ : x ∈ (λ[ f (𝔹𝔹) ] var f · var x)
example-free₁ = free-λ f≢x (free-·₂ free-var)
example-free₁ : x ∈ (λ[ f (𝔹𝔹) ] ` f · ` x)
example-free₁ = free-λ f≢x (free-·₂ free-`)
example-free₂ : f ∉ (λ[ f (𝔹𝔹) ] var f · var x)
example-free₂ : f ∉ (λ[ f (𝔹𝔹) ] ` f · ` x)
example-free₂ (free-λ f≢f _) = f≢f refl
\end{code}
@ -240,76 +240,75 @@ Prove formally the remaining examples given above.
\begin{code}
postulate
example-free₃ : x ∈ ((λ[ f (𝔹𝔹) ] var f · var x) · var f)
example-free₄ : f ∈ ((λ[ f (𝔹𝔹) ] var f · var x) · var f)
example-free₅ : x ∉ (λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] var f · var x)
example-free₆ : f ∉ (λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] var f · var x)
example-free₃ : x ∈ ((λ[ f (𝔹𝔹) ] ` f · ` x) · ` f)
example-free₄ : f ∈ ((λ[ f (𝔹𝔹) ] ` f · ` x) · ` f)
example-free₅ : x ∉ (λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] ` f · ` x)
example-free₆ : f ∉ (λ[ f (𝔹𝔹) ] λ[ x 𝔹 ] ` f · ` x)
\end{code}
Although `_∈_` may apperar to be a low-level technical definition,
Although `_∈_` may appear to be a low-level technical definition,
understanding it is crucial to understanding the properties of
substitution, which are really the crux of the lambda calculus.
### Substitution
To prove that substitution preserves typing, we first need a
technical lemma connecting free variables and typing contexts: If
a variable `x` appears free in a term `M`, and if we know `M` is
well typed in context `Γ`, then it must be the case that
`Γ` assigns a type to `x`.
To prove that substitution preserves typing, we first need a technical
lemma connecting free variables and typing contexts. If variable `x`
appears free in term `M`, and if `M` is well typed in context `Γ`,
then `Γ` must assign a type to `x`.
\begin{code}
freeLemma : ∀ {x M A Γ} → x ∈ M → Γ ⊢ M A → ∃ λ B → Γ x ≡ just B
\end{code}
_Proof_: We show, by induction on the proof that `x` appears
free in `P`, that, for all contexts `Γ`, if `P` is well
free in `M`, that, for all contexts `Γ`, if `M` is well
typed under `Γ`, then `Γ` assigns some type to `x`.
- If the last rule used was `free-var`, then `P = x`, and from
- If the last rule used was `free-\``, then `M = \` x`, and from
the assumption that `M` is well typed under `Γ` we have
immediately that `Γ` assigns a type to `x`.
- If the last rule used was `free-·₁`, then `P = L · M` and `x`
appears free in `L`. Since `L` is well typed under `\Gamma`,
- If the last rule used was `free-·₁`, then `M = L · M` and `x`
appears free in `L`. Since `L` is well typed under `Γ`,
we can see from the typing rules that `L` must also be, and
the IH then tells us that `Γ` assigns `x` a type.
- Almost all the other cases are similar: `x` appears free in a
subterm of `P`, and since `P` is well typed under `Γ`, we
subterm of `M`, and since `M` is well typed under `Γ`, we
know the subterm of `M` in which `x` appears is well typed
under `Γ` as well, and the IH gives us exactly the
conclusion we want.
under `Γ` as well, and the IH yields the desired conclusion.
- The only remaining case is `free-λ`. In this case `P =
- The only remaining case is `free-λ`. In this case `M =
λ[ y A ] N`, and `x` appears free in `N`; we also know that
`x` is different from `y`. The difference from the previous
cases is that whereas `P` is well typed under `\Gamma`, its
cases is that whereas `M` is well typed under `Γ`, its
body `N` is well typed under `(Γ , y A)`, so the IH
allows us to conclude that `x` is assigned some type by the
extended context `(Γ , y A)`. To conclude that `Γ`
assigns a type to `x`, we appeal the decidable equality for names
`_≟_`, noting that `x` and `y` are different variables.
`_≟_`, and note that `x` and `y` are different variables.
\begin{code}
freeLemma free-var (Ax Γx≡justA) = (_ , Γx≡justA)
freeLemma free-` (Ax Γx≡A) = (_ , Γx≡A)
freeLemma (free-·₁ x∈L) (⇒-E ⊢L ⊢M) = freeLemma x∈L ⊢L
freeLemma (free-·₂ x∈M) (⇒-E ⊢L ⊢M) = freeLemma x∈M ⊢M
freeLemma (free-if₁ x∈L) (𝔹-E ⊢L ⊢M ⊢N) = freeLemma x∈L ⊢L
freeLemma (free-if₂ x∈M) (𝔹-E ⊢L ⊢M ⊢N) = freeLemma x∈M ⊢M
freeLemma (free-if₃ x∈N) (𝔹-E ⊢L ⊢M ⊢N) = freeLemma x∈N ⊢N
freeLemma (free-λ {x} {y} y≢x x∈N) (⇒-I ⊢N) with freeLemma x∈N ⊢N
... | Γx=justC with y ≟ x
... | ΓxC with y ≟ x
... | yes y≡x = ⊥-elim (y≢x y≡x)
... | no _ = Γx=justC
... | no _ = ΓxC
\end{code}
[A subtle point: if the first argument of `free-λ` was of type
A subtle point: if the first argument of `free-λ` was of type
`x ≢ y` rather than of type `y ≢ x`, then the type of the
term `Γx=justC` would not simplify properly.]
term `Γx≡C` would not simplify properly; instead, one would need
to rewrite with the symmetric equivalence.
Next, we'll need the fact that any term `M` which is well typed in
the empty context is closed (it has no free variables).
As a second technical lemma, we need that any term `M` which is well
typed in the empty context is closed (has no free variables).
#### Exercise: 2 stars, optional (∅⊢-closed)
@ -325,16 +324,16 @@ contradiction ()
∅⊢-closed : ∀ {M A} → ∅ ⊢ M A → closed M
∅⊢-closed {M} {A} ⊢M {x} x∈M with freeLemma x∈M ⊢M
... | (B , ∅x≡justB) = contradiction (trans (sym ∅x≡justB) (apply-∅ x))
... | (B , ∅x≡B) = contradiction (trans (sym ∅x≡B) (apply-∅ x))
\end{code}
</div>
Sometimes, when we have a proof `Γ ⊢ M A`, we will need to
replace `Γ` by a different context `Γ′`. When is it safe
to do this? Intuitively, it must at least be the case that
`Γ′` assigns the same types as `Γ` to all the variables
that appear free in `M`. In fact, this is the only condition that
is needed.
to do this? Intuitively, the only variables we care about
in the context are those that appear free in `M`. So long
as the two contexts agree on those variables, one can be
exchanged for the other.
\begin{code}
contextLemma : ∀ {Γ Γ′ M A}
@ -343,50 +342,52 @@ contextLemma : ∀ {Γ Γ′ M A}
→ Γ′ ⊢ M A
\end{code}
_Proof_: By induction on the derivation of
`Γ ⊢ M A`.
_Proof_: By induction on the derivation of `Γ ⊢ M A`.
- If the last rule in the derivation was `var`, then `t = x`
and `\Gamma x = T`. By assumption, `\Gamma' x = T` as well, and
hence `\Gamma' \vdash t : T` by `var`.
- If the last rule in the derivation was `Ax`, then `M = x`
and `Γ x ≡ just A`. By assumption, `Γ′ x = just A` as well, and
hence `Γ′ ⊢ M : A` by `Ax`.
- If the last rule was `abs`, then `t = \lambda y:A. t'`, with
`T = A\to B` and `\Gamma, y : A \vdash t' : B`. The
induction hypothesis is that, for any context `\Gamma''`, if
`\Gamma, y:A` and `\Gamma''` assign the same types to all the
free variables in `t'`, then `t'` has type `B` under
`\Gamma''`. Let `\Gamma'` be a context which agrees with
`\Gamma` on the free variables in `t`; we must show
`\Gamma' \vdash \lambda y:A. t' : A\to B`.
- If the last rule was `⇒-I`, then `M = λ[ y : A] N`, with
`A = A ⇒ B` and `Γ , y A ⊢ N B`. The
induction hypothesis is that, for any context `Γ″`, if
`Γ , y : A` and `Γ″` assign the same types to all the
free variables in `N`, then `N` has type `B` under
`Γ″`. Let `Γ′` be a context which agrees with
`Γ` on the free variables in `N`; we must show
`Γ′ ⊢ λ[ y A] N A ⇒ B`.
By `abs`, it suffices to show that `\Gamma', y:A \vdash t' : t'`.
By the IH (setting `\Gamma'' = \Gamma', y:A`), it suffices to show
that `\Gamma, y:A` and `\Gamma', y:A` agree on all the variables
that appear free in `t'`.
By `⇒-I`, it suffices to show that `Γ′ , y:A ⊢ N B`.
By the IH (setting `Γ″ = Γ′ , y : A`), it suffices to show
that `Γ , y : A` and `Γ′ , y : A` agree on all the variables
that appear free in `N`.
Any variable occurring free in `t'` must be either `y` or
some other variable. `\Gamma, y:A` and `\Gamma', y:A`
clearly agree on `y`. Otherwise, note that any variable other
than `y` that occurs free in `t'` also occurs free in
`t = \lambda y:A. t'`, and by assumption `\Gamma` and
`\Gamma'` agree on all such variables; hence so do `\Gamma, y:A` and
`\Gamma', y:A`.
Any variable occurring free in `N` must be either `y` or
some other variable. Clearly, `Γ , y : A` and `Γ′ , y : A`
agree on `y`. Otherwise, any variable other
than `y` that occurs free in `N` also occurs free in
`λ[ y : A] N`, and by assumption `Γ` and
`Γ′` agree on all such variables; hence so do
`Γ , y : A` and `Γ′ , y : A`.
- If the last rule was `app`, then `t = t_1\;t_2`, with
`\Gamma \vdash t_1:A\to T` and `\Gamma \vdash t_2:A`.
One induction hypothesis states that for all contexts `\Gamma'`,
if `\Gamma'` agrees with `\Gamma` on the free variables in `t_1`,
then `t_1` has type `A\to T` under `\Gamma'`; there is a similar IH
for `t_2`. We must show that `t_1\;t_2` also has type `T` under
`\Gamma'`, given the assumption that `\Gamma'` agrees with
`\Gamma` on all the free variables in `t_1\;t_2`. By `app`, it
suffices to show that `t_1` and `t_2` each have the same type
under `\Gamma'` as under `\Gamma`. But all free variables in
`t_1` are also free in `t_1\;t_2`, and similarly for `t_2`;
hence the desired result follows from the induction hypotheses.
- If the last rule was `⇒-E`, then `M = L · M`, with `Γ ⊢ L A ⇒ B`
and `Γ ⊢ M B`. One induction hypothesis states that for all
contexts `Γ′`, if `Γ′` agrees with `Γ` on the free variables in
`L` then `L` has type `A ⇒ B` under `Γ′`; there is a similar IH
for `M`. We must show that `L · M` also has type `B` under `Γ′`,
given the assumption that `Γ′` agrees with `Γ` on all the free
variables in `L · M`. By `⇒-E`, it suffices to show that `L` and
`M` each have the same type under `Γ′` as under `Γ`. But all free
variables in `L` are also free in `L · M`; in the proof, this is
expressed by composing `free-·₁ : ∀ {x} → x ∈ L → x ∈ L · M` with
`Γ~Γ′ : (∀ {x} → x ∈ L · M → Γ x ≡ Γ′ x)` to yield `Γ~Γ′ ∘ free-·₁
: ∀ {x} → x ∈ L → Γ x ≡ Γ′ x`. Similarly for `M`; hence the
desired result follows from the induction hypotheses.
- The remaining cases are similar to `⇒-E`.
\begin{code}
contextLemma Γ~Γ′ (Ax Γx≡justA) rewrite (Γ~Γ′ free-var) = Ax Γx≡justA
contextLemma Γ~Γ′ (Ax Γx≡A) rewrite (Γ~Γ′ free-`) = Ax Γx≡A
contextLemma {Γ} {Γ′} {λ[ x A ] N} Γ~Γ′ (⇒-I ⊢N) = ⇒-I (contextLemma Γx~Γx ⊢N)
where
Γx~Γx : ∀ {y} → y ∈ N → (Γ , x A) y ≡ (Γ′ , x A) y
@ -398,26 +399,6 @@ contextLemma Γ~Γ′ 𝔹-I₁ = 𝔹-I₁
contextLemma Γ~Γ′ 𝔹-I₂ = 𝔹-I₂
contextLemma Γ~Γ′ (𝔹-E ⊢L ⊢M ⊢N)
= 𝔹-E (contextLemma (Γ~Γ′ ∘ free-if₁) ⊢L) (contextLemma (Γ~Γ′ ∘ free-if₂) ⊢M) (contextLemma (Γ~Γ′ ∘ free-if₃) ⊢N)
{-
replaceCtxt f (var x xA
) rewrite f var = var x xA
replaceCtxt f (app t₁A⇒B t₂A)
= app (replaceCtxt (f ∘ app1) t₁A⇒B) (replaceCtxt (f ∘ app2) t₂A)
replaceCtxt {Γ} {Γ′} f (abs {.Γ} {x} {A} {B} {t} tB)
= abs (replaceCtxt f tB)
where
f : ∀ {y} → y ∈ t → (Γ , x A) y ≡ (Γ′ , x A) y
f {y} y∈t with x ≟ y
... | yes _ = refl
... | no x≠y = f (abs x≠y y∈t)
replaceCtxt _ true = true
replaceCtxt _ false = false
replaceCtxt f (if t₁bool then t₂A else t₃A)
= if replaceCtxt (f ∘ if1) t₁bool
then replaceCtxt (f ∘ if2) t₂A
else replaceCtxt (f ∘ if3) t₃A
-}
\end{code}
@ -590,18 +571,18 @@ _Proof_: By induction on the derivation of `\vdash t : T`.
follows directly from the induction hypothesis.
\begin{code}
preservation (Ax x₁) ()
preservation (Ax Γx≡A) ()
preservation (⇒-I ⊢N) ()
preservation (⇒-E (⇒-I ⊢N) ⊢V) (β valueV) = preservation-[=] ⊢N ⊢V
preservation (⇒-E ⊢L ⊢M) (γ⇒₁ L⟹L) with preservation ⊢L L⟹L
preservation (⇒-E (⇒-I ⊢N) ⊢V) (βλ· valueV) = preservation-[=] ⊢N ⊢V
preservation (⇒-E ⊢L ⊢M) (ξ·₁ L⟹L) with preservation ⊢L L⟹L
...| ⊢L = ⇒-E ⊢L ⊢M
preservation (⇒-E ⊢L ⊢M) (γ⇒₂ valueL M⟹M) with preservation ⊢M M⟹M
preservation (⇒-E ⊢L ⊢M) (ξ·₂ valueL M⟹M) with preservation ⊢M M⟹M
...| ⊢M = ⇒-E ⊢L ⊢M
preservation 𝔹-I₁ ()
preservation 𝔹-I₂ ()
preservation (𝔹-E 𝔹-I₁ ⊢M ⊢N) β𝔹₁ = ⊢M
preservation (𝔹-E 𝔹-I₂ ⊢M ⊢N) β𝔹₂ = ⊢N
preservation (𝔹-E ⊢L ⊢M ⊢N) (γ𝔹 L⟹L) with preservation ⊢L L⟹L
preservation (𝔹-E 𝔹-I₁ ⊢M ⊢N) βif-true = ⊢M
preservation (𝔹-E 𝔹-I₂ ⊢M ⊢N) βif-false = ⊢N
preservation (𝔹-E ⊢L ⊢M ⊢N) (ξif L⟹L) with preservation ⊢L L⟹L
...| ⊢L = 𝔹-E ⊢L ⊢M ⊢N
\end{code}